The Fruit Malus prunifolia (Malus micromalus Mak.): A Minireview of Current Knowledge of Fruit Composition and Health Benefits - Xiaolong Ji; Chunyan Hou; Xudan Guo (Journal of Chemistry)
The fruit Malus prunifolia (Malus micromalus Mak.), which belongs to the Rosaceae family, grows mostly in the upper-middle reaches of the Yellow River area. It has long been popular as a fruit commodity and as a natural remedy. Its main biologically active components include vitamin C, phenolics, flavonoids, polysaccharides, and triterpenic acids. Recent phytochemical studies on the fruit have shed some light on its biological activities, such as anticancer, immunomodulatory, antioxidant, immunostimulating, hepatoprotective, and gastrointestinal protective activities. A stronger focus on clinical studies and phytochemical characterization of the fruit will be essential for future research efforts. This minireview could be useful for predicting its other medicinal uses and its potential drug or food interactions, and it could be beneficial for people living in areas where the fruit is endemic and where healthcare resources are scarce.